Biphasic decay of the Ca transient results from increased sarcoplasmic reticulum Ca leak. (6th January 2016) - Sankaranarayanan, Rajiv; Li, Yatong; Greensmith, David J.; Eisner, David A.; Venetucci, Luigi
Abstract : Key points: Ca leak from the sarcoplasmic reticulum through the ryanodine receptor (RyR) reduces the amplitude of the Ca transient and slows its rate of decay. In the presence of β‐adrenergic stimulation, RyR‐mediated Ca leak produces a biphasic decay of the Ca transient with a fast early phase and a slow late phase. Two forms of Ca leak have been studied, Ca‐sensitising (induced by caffeine) and non‐sensitising (induced by ryanodine) and both induce biphasic decay of the Ca transient. Only Ca‐sensitising leak can be reversed by traditional RyR inhibitors such as tetracaine. Ca leak can also induce Ca waves. At low levels of leak, waves occur. As leak is increased, first biphasic decay and then slowed monophasic decay is seen. The level of leak has major effects on the shape of the Ca transient. Abstract: In heart failure, a reduction in Ca transient amplitude and contractile dysfunction can by caused by Ca leak through the sarcoplasmic reticulum (SR) Ca channel (ryanodine receptor, RyR) and/or decreased activity of the SR Ca ATPase (SERCA). We have characterised the effects of two forms of Ca leak (Ca‐sensitising and non‐sensitising) on calcium cycling and compared with those of SERCA inhibition. We measured [Ca 2+ ]i with fluo‐3 in voltage‐clamped rat ventricular myocytes. Increasing SR leak with either caffeine (to sensitise the RyR to Ca activation) or ryanodine (non‐sensitising) had similar effects to SERCA inhibition: decreased systolic [Ca 2+ ]i, increased diastolic [Ca 2+ ]i and slowed decay. However, in the presence of isoproterenol, leak produced a biphasic decay of the Ca transient in the majority of cells while SERCA inhibition produced monophasic decay. Tetracaine reversed the effects of caffeine but not of ryanodine. When caffeine (1 mmol l −1 ) was added to a cell which displayed Ca waves, the wave frequency initially increased before waves disappeared and biphasic decay developed. Eventually (at higher caffeine concentrations), the biphasic decay was replaced by slow decay. We conclude that, in the presence of adrenergic stimulation, Ca leak can produce biphasic decay; the slow phase results from the leak opposing Ca uptake by SERCA. The degree of leak determines whether decay of Ca waves, biphasic or monophasic, occurs. Key points: Ca leak from the sarcoplasmic reticulum through the ryanodine receptor (RyR) reduces the amplitude of the Ca transient and slows its rate of decay. In the presence of β‐adrenergic stimulation, RyR‐mediated Ca leak produces a biphasic decay of the Ca transient with a fast early phase and a slow late phase. Two forms of Ca leak have been studied, Ca‐sensitising (induced by caffeine) and non‐sensitising (induced by ryanodine) and both induce biphasic decay of the Ca transient. Only Ca‐sensitising leak can be reversed by traditional RyR inhibitors such as tetracaine. Ca leak can also induce Ca waves. At low levels of leak, waves occur. As leak is increased, first biphasic decay and then slowed monophasic decay is seen. The level of leak has major effects on the shape of the Ca transient.